Young Investigator: Aaron Hernandez-Santana. (May 2009) - Hernandez-Santana, Aaron; McMahon, Gillian
Supervisor's supporting comments: Dr Aaron Hernandez-Santana is a creative, dynamic and enthusiastic researcher and I know that he will go far in his career, wherever that may take him. His work in the Bioanalytical Chemistry and Diagnostics research group at Dublin City University, Ireland, has been innovative and he uses his experience in new and exciting ways, meaning he always brings value to his research. Aaron is truly a problem-solving bioanalytical investigator – he works easily with other disciplines, he applies his chemistry knowledge to physics and biology applications, he is not afraid to move outside his comfort zone of research expertise, acquiring new skills as and when he needs them and he has some great ideas that will serve him well in the future.